2016
DOI: 10.1371/journal.pgen.1005844
|View full text |Cite
|
Sign up to set email alerts
|

Nucleolar DEAD-Box RNA Helicase TOGR1 Regulates Thermotolerant Growth as a Pre-rRNA Chaperone in Rice

Abstract: Plants have evolved a considerable number of intrinsic tolerance strategies to acclimate to ambient temperature increase. However, their molecular mechanisms remain largely obscure. Here we report a DEAD-box RNA helicase, TOGR1 (Thermotolerant Growth Required1), prerequisite for rice growth themotolerance. Regulated by both temperature and the circadian clock, its expression is tightly coupled to daily temperature fluctuations and its helicase activities directly promoted by temperature increase. Located in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
81
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 93 publications
(87 citation statements)
references
References 68 publications
2
81
0
2
Order By: Relevance
“…Wang et al . () also demonstrated that genetic variations in ZmVPP1 contribute to drought tolerance in maize seedlings. In the present research, we found that inbred lines with Hap3 had a significantly longer kernel length than those with Hap1 and Hap2 on the basis of candidate gene‐based association analysis using data from a panel of 479 maize genotypes.…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…Wang et al . () also demonstrated that genetic variations in ZmVPP1 contribute to drought tolerance in maize seedlings. In the present research, we found that inbred lines with Hap3 had a significantly longer kernel length than those with Hap1 and Hap2 on the basis of candidate gene‐based association analysis using data from a panel of 479 maize genotypes.…”
Section: Discussionmentioning
confidence: 89%
“…In Arabidopsis, both P-A3 and 32S pre-rRNA intermediates can be detected during pre-rRNA processing, indicating that the two pre-rRNA processing pathways also co-exist in this plant (Hang et al, 2014;Weis et al, 2015b). In rice, however, only the intermediate of P-A3 has been detected, suggesting that the 'preferential cleavage in ITS1 before the complete removal of the 5 0 ETS' is the main pathway for pre-rRNA processing (Wang et al, 2016a). In the present research, we detected the intermediates of both P-A3 and 32S rRNA in maize by northern blot and/or cRT-PCR, demonstrating that the two pre-rRNA processing pathways co-exist in maize.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…In the Neurospora clock, FRQ-interacting RNA Helicase (FRH)’s primary role is to mediate a proper contact among FRQ, CK1a and WCC (Hurley et al, 2013; Lauinger et al, 2014; Conrad et al, 2016). TOGR1, a DEAD-box helicase in the rice plant, is involved in temperature-dependent and clock-controlled plant growth through stabilizing rRNA homeostasis (Wang et al, 2016). DDX5, an ortholog of PRD-1, is associated in the PER complex, and regulates per RNA metabolism and its clock function (Padmanabhan et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…DEAD-box proteins comprise a large protein family and are involved in almost all nucleic acid metabolic activities, including replication, repair, recombination, transcription, translation, ribosome biogenesis, and splicing [47,48]. It has been reported that the DEAD-box proteins play important roles in plant growth and development, as well as abiotic (10 of 12) 1600365 stress response [49][50][51]. In the present study, we reported that DEAD-box ATP-dependent RNA helicase 20 is involved in rice response to HNT stress, and RNA helicase 20 was upregulated by over 1.7-fold in the HTL and downregulated by 1.5-fold (1/0.658) in the HSL, compared to the controls, respectively.…”
Section: Transcript Regulation Proteins Were Upregulated In the Htl Amentioning
confidence: 99%